Does social welfare influence economic growth? Study for 17 countries of Latin America in the period 2014-2018 - Cuesta, Lizeth (2021)
At the global level, the well-being of society still maintains imbalances both within and between nations. For this reason, the Social Progress Index seeks to measure the quality of life of a society. In this way, the study aims to determine the relationship between economic growth and IPS in the 2014-2018 period for 17 Latin American countries. For this, the econometric technique of panel data using Generalized Least Squares was used to avoid problems of autocorrelation and heteroscedasticity in the model. Likewise, information was collected from the databases of the Social Progress Imperative (2018) and the World Bank (2018) and the various components of the IPS were considered in order to determine which of them has the greatest effect on economic growth. Among the main results, it stands out that the hypothesis is fulfilled when verifying that the IPS has a positive impact on economic growth, although the significance of its dimensions varies according to income level. Given this, the policy implications should focus on greater attention to health, education, the environment and, above all, anti-corruption laws that prevent the diversion of resources and harm the well-being of society.